Personal Growth Initiative - Edan, Ayad Kareem; Al-Khayri, Arwa Muhammad Rabee’ (Al-Adab Journal, 2022)
The Personal Growth Initiative is ’the active and deliberate participation in the process of personal growth often referred to as an advanced set of skills that intentionally help a person improve self-cohesion and develop talents and potentials. The current research aims at identifying: Measuring the initiative for personal growth among state employees. 2- The significance of the statistical differences in the initiative of personal growth among state employees according to a variable A- For gender (male-female) B- Age. C- Marital Status (Single, Married) To order to achieve the objectives of the current research, the researcher adopted the personal growth initiative scale according to The Rupchik theory, which consists of 16 paragraphs in its final form and has been verified as authenticity and consistency. The scale was applied in its final form to the research sample of 400 employees and for both types, which were selected in the random class method, and after applying the research tool and using statistical methods, the T test for one sample, the T test for two independent samples, and the Pearson correlation factor. The results that the study has come up with are as follows: State employees have a personal growth initiative. There are no differences according to (gender, age, marital status) for the Personal Growth Initiative. The researcher suggested a set of recommendations and suggestions.